In-situ electron microscopy mapping of an order-disorder transition in a superionic conductor - Jaeyoung Heo (Nature Portfolio, 2019)
Solid-solid phase transitions are processes ripe for the discovery of correlated atomic motion in crystals. Here, the authors monitor an order-disorder transition in real-time in a single nanoparticle of the super-ionic solid, cuprous selenide, using in-situ high-resolution transmission electron microscopy.